COMPARATIVE STUDY OF CONSUMER PREFERENCES BETWEEN GARUDA AIRLINES AND BATIK AIR - Liempepas, Silvia .; Tumbuan, Willem J.F.A; Rumokoy, Farlane S (Universitas Sam Ratulangi, 2017)
Abstract: For the full service airlines in Manado are serve by two airlines, which is Garuda and Â Batik Air. The Research results are expected to be use as a reference for future research primarily on how the comparison between the airlines with full services to become a consumer choice in air transportation. There are 130 respondents from passengers who have experience flight with Garuda Airline and Batik Air. By using Independent Sample t Test the result shows that there is significant difference on Consumer Preference measured by Service Quality, Luggage Capacity, Price and Comfort, meanwhile there is no significant difference on Consumer Preference measured by Ease of Online Booking. For Garuda Airlines and Batik Air as full service airlines should pay attention all of the customer preferences and must continue to keep evaluating and maintaining each aspect. Batik Air should keep improving and developing more because they lack behind Garuda Airlines in points of Service Quality, Luggage Capacity, Price and Comfort. For Garuda Airlines, they should maintain the advantage that they have ahead from Batik Air such as Service Quality and Comfort.Keywords: Consumer Preferences, Airlines